(untitled) - Mader, Sylvia S. (Boston, 2007)
"Biology" is a comprehensive introductory biology textbook for non-majors or mixed-majors courses that covers biology in a traditional order from the structure and function of the cell to the organization of the biosphere. The book, which centers on the evolution and diversity of organisms, is appropriate for a one- or two-semester course. It's no wonder that Sylvia Mader's "Biology" continues to be a text that's appreciated as much by instructors as it is by the students who use it.
Keywords: Biology,Sinh vật học.